Effect of hydrostatic pressure and magnetic field on electromagnetically induced transparency based nonlinear frequency conversion in quantum ring. (October 2016) - Gumber, Sukirti; Gambhir, Monica; Jha, Pradip Kumar; Mohan, Man
Abstract: We study the combined effect of hydrostatic pressure and magnetic field on electromagnetically induced transparency in quantum ring. The high flexibility in size and shape of ring makes it possible to fabricate a nearly perfect two-dimensional quantum structure. We also explore the dependence of frequency conversion, measured in terms of third order nonlinear susceptibility χ ( 3 ), on coupling field, hydrostatic pressure and magnetic field. Although, a dip in χ ( 3 ) is observed with the introduction of strong coupling field, it renders the ring structure transparent to generated wave thus effectively enhancing the output of nonlinear frequency conversion process. At a fixed coupling strength, the output can be further enhanced by increasing the magnetic field while it shows an inverse relationship with pressure. These parameters, being externally controlled, provide an easy handle to control the output of quantum ring which can be used as frequency converter in communication networks. Highlights: EIT based sum frequency generation is studied in 2D quantum ring of finite width. The efficiency of nonlinear frequency conversion is observed to be enhanced by EIT. The nonlinear susceptibility χ ( 3 ) is found to be strongly dependent on coupling strength. At a fixed coupling field, magnetic field further enhances the efficiency. Sum-frequency output and its absorption depend inversely on hydrostatic pressure.